1998
DOI: 10.1038/sj.leu.2401166
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of H+-ATPase-dependent activity of multidrug resistance-associated protein in homoharringtonine-resistant human leukemic K562 cells

Abstract: Multidrug resistance (MDR), caused by overexpression of either P-glycoprotein or the multidrug resistance-associated protein (MRP), is characterized by a decreased cellular drug accumulation due to an enhanced drug efflux. Many studies on cells overexpressing MRP and/or Pgp, have shown a concentration of the drug inside cytoplasmic acidic vesicles followed by an exocytotic process. In this study, we examined the effects of 7-chloro-4-nitrobenzo-2-oxa-1, 3-diazole or NBD (a H + -ATPase pump inhibitor), buthioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…[98] Previous reports have noted that the activity of homoharringtonine (3), the cephalotaxus ester currently being evaluated in clinical trials, is also compromised in MDR human leukemia cells. [18] Remarkably, the susceptibility of MDR cancer cells to different Cephalotaxus esters has not been systematically probed. Prevention of MDR would significantly improve therapeutic response to this family of chemotherapeutics and extend their use in the clinic.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 1 more Smart Citation
“…[98] Previous reports have noted that the activity of homoharringtonine (3), the cephalotaxus ester currently being evaluated in clinical trials, is also compromised in MDR human leukemia cells. [18] Remarkably, the susceptibility of MDR cancer cells to different Cephalotaxus esters has not been systematically probed. Prevention of MDR would significantly improve therapeutic response to this family of chemotherapeutics and extend their use in the clinic.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…These results prompted Phase I clinical evaluation of homoharringtonine (3) in the US in 1981, [16] advancing to more recent phase II studies. [17] While difficulties in production, coupled with its hematologic toxicity and susceptibility to multidrug resistance (MDR), [18] have hindered the development of 3, it is still viewed as a useful drug for the treatment of chronic myeloid leukemia in combination therapy. [17] Cephalotaxine (1) has received considerable and enduring attention in the arena of total synthesis.…”
mentioning
confidence: 99%
“…Although it is possible that the flow cytometry technique was insufficiently sensitive to detect low levels of Pgp expressionthus leading to false-negative results-it may be more likely that the mechanism of Hoechst dye efflux is more complex than previously thought, perhaps involving ABC transporter molecules sensitive to verapamil inhibition, such as the multidrug resistance protein or breast cancer-related protein or unknown molecules. [37][38][39] Additional studies designed to elucidate the molecular mechanisms involved in Hoechst dye efflux will be necessary to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…72 Other modulators such as genistein, a specific inhibitor of tyrosine kinase, or 7-chloro-4-notrobenz-2-oxa-1,3-diazole (NBD), a vacuolar H+-ATPase, have been reported to modulate MRP1 of a non-specific manner. [73][74][75] However, genistein showed major differences in effects on Rh123 vs DNR transport in the MRP1-mediated MDR cell lines: the accumulation of DNR was increased, whereas the accumulation of Rh123 was decreased by genistein. 73 Recently, van der Kolk et al 40 and ourselves 11 have demonstrated that MRP1 was functional in fresh acute myeloid leukemic blast cells using CF and calcein-AM, respectively.…”
Section: Mrp1 Activity In Amlmentioning
confidence: 99%